2017
DOI: 10.1590/1678-7757-2016-0634
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effect of mineral aggregate-based cements: histopathological analysis in rats

Abstract: Objective:Several studies reported the local tissue reaction caused by mineral aggregate-based cements. However, few studies have investigated the systemic effects promoted by these cements on liver and kidney when directly applied to connective tissue. The purpose of this in vivo study was to investigate the systemic effect of mineral aggregate-based cements on the livers and kidneys of rats.Material and Methods:Samples of Mineral Trioxide Aggregate (MTA) and a calcium aluminate-based cement (EndoBinder) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Our results also showed that the density of the fibrous capsule increased over the course of time. The fibrous capsule became more organized, with lower number of fibroblasts among the fibers, confirming similar literature results (Aguilar et al, 2012;de Souza Costa et al, 2014;Garcia et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results also showed that the density of the fibrous capsule increased over the course of time. The fibrous capsule became more organized, with lower number of fibroblasts among the fibers, confirming similar literature results (Aguilar et al, 2012;de Souza Costa et al, 2014;Garcia et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The histopathological analysis was performed in a double-blind man- The amount of polymorph-and mononuclear cells, lymphocytes, macrophages, giant multinucleate cells and congested capillaries was considered to grade the severity of the inflammatory reaction (absent, mild, moderate or severe) (Aguilar et al, 2012;de Souza Costa et al, 2014;Garcia et al, 2017;Garcia, Huck, et al, 2014). Based on these histopathological features, the following criteria was used to grade the tissue reaction: −0inflammation absent (0-10 inflammatory cells/area); −1mild inflammation (11-25 cells); −2moderate inflammation (26-65 cells); and − 3-severe inflammation (more than 65 inflammatory cells/area) (Aguilar et al, 2012;de Souza Costa et al, 2014;Garcia et al, 2017;Garcia, Huck, et al, 2014).…”
Section: Histopathological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…12,64 Therefore, studies have been conducted to evaluate the potential risks of these materials to body organs. 11,62,64,65,66 Al-Hiyasat et al 67 suggested that leached substances from resin-based dental composite materials have an adverse effect on the fertility and reproductive system of male mice. Fakhouri et al 68 demonstrated that the administration of high concentrations of methyl methacrylate is associated with seminal vesicle atrophy in rats.…”
Section: Systemic Conditions and Their Relationships With Dental Matementioning
confidence: 99%
“…Kidney function was not affected, but a continuous increase in the liver function markers was detected in the presence of MTA. In a similar investigation, the systemic effects of MTA and EndoBinder were also evaluated in the liver and kidney by Garcia et al 66 They reported that both sealers caused severe inflammatory reactions in the body organs, but in the MTA group, these reactions were more accentuated. In addition, an increase in liver function marker levels was also detected in the presence of MTA.…”
Section: Systemic Conditions and Their Relationships With Dental Matementioning
confidence: 99%